Selected highlights of 2001: A few IPGRI projects selected as worthy of special note - International Plant Genetic Resources Institute (2002)
Selected highlights of 2001 is a multi-language publication detailing some of IPGRI's key projects and achievements in 2001. This full-colour, illustrated brochure includes French, Spanish, Italian, English, Russian, Arabic, Chinese and Japanese texts and is intended as an overview of the Annual Report (available in English). Projects covered include EPGRIS, INIBAP's banana genome project, the global cacoa project, wild rice diversity mapping and the desert margins project.